Evaluation Of Diabetic Management Outcome And Pharmacist Intervention In Pulau Pinang, Malaysia - Gillani, Syed Wasif (2013)
The objectives of the study were to evaluate clinical disease management outcome and patient responsiveness to treatment. The primary current study is classified as ‘mixedmethodology’ cross sectional interventional study, which includes four phases of evaluation with different methodologies. Phase I (retrospective evaluation), Phase II (prospective pharmaceutical care application), Phase III (prospective case-control cohort evaluation) and Phase IV (Psychometric population based survey). During the time period of January 2008 through December 2010, a total of 2174 diabetes patients were admitted; 2174 (100%) patients’ medical profiles were reviewed. This comprised of 1063 (48.9%) males and rest 1111 (51.1%) females. Mean and Standard Distribution (SD) should females have less mean age distribution (35.2 ±4.187 years) as compared to males (37.9±5.724 years). A total of 798 (36.7%) had infection exposure before and/or during hospital admission, statistical significance (p<0.001) found in association of diabetes ketoacidosis (DKA) and infection exposure. Majority 384 (48.1%) infection type was relapsed cases within 3 months. There were 176 with presumed viral infection (18.2%), and 679 with bacterial infection (70.2%). Of those with bacterial infection, 453 had minor infection (66.7%), and 226 had major infection (33.3%). In prospective pharmaceutical care study, two hundred and fifty three patients from the Diabetes Outpatient clinic Hospital Pulau Pinang were recruited, comprising 127 cases and 126 controls. There were no significant differences between cases and controls for any of the demographic variables that were documented.